The Effectiveness of Wordwall in Increasing Student Engagement in Elementary Social Studies Education Course at West Sulawesi University - Iqbal Arifin; Darman Manda (Universitas Negeri Makassar, 2024)
The COVID-19 pandemic is disrupting traditional education and forcing educators to turn to distance and online learning. This research examines the effectiveness of Wordwall, an interactive platform, in increasing student engagement in Social Studies Education courses at the University of West Sulawesi. The research method used is qualitative with observation and interview techniques. Data were collected from eight students of the Elementary School Teacher Education study program who were selected based on their engagement in class, previous experience with online learning, and willingness to participate. The results showed that the use of Wordwall significantly increased students' engagement and motivation. Interactive features such as Quiz, Match Up, and Random Wheel help to create more interesting and varied learning activities. It is recommended that educators use Wordwall features more frequently, conduct training to improve skills in using this platform, and utilize the analysis feature to provide more specific and timely feedback. The integration of Wordwall in learning can create a more dynamic and engaging learning experience, thus helping students achieve better learning outcomes. This research provides important insights into how interactive technologies can be effectively used in higher education to improve student participation and learning outcomes.